KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS MENSTRUATION OF MIDWIFERY STUDENTS IN SURABAYA - Mega Merdeka Pertiwi; Nur Ainy Fardana Nawangsari; Irwanto Irwanto (Indonesian Midwifery and Health Sciences Journal, 2020)
Abstract Background: population of reproductive women in the world reach 52% (House, et al., 2012), while in Surabaya reach 24,6% (BPS, 2019). Menstruation is a natural aspect of reproductive woman’s life and becomes a very critical point because it shows the basis of women’s wellbeing, especially menstrual hygiene. Poor hygiene during menstruation can lead to reproductive tract infection. In order to avoid RTI, good menstrual behavior is needed. Midwifery students as future health workers will be a role in helping change people’s behavior, one of which practice of menstruation towards better. Aims: This research to find out knowledge, attitudes and practices about menstruation of midwifery students in Surabaya. Methods: this research method is descriptive quantitative cross-sectional, with a sample of the first level midwifery students from five institutions in Surabaya. Sampling with total sampling and which includes inclusion criteria is 206 respondents. This research has been held in September- October 2019. The variables are knowledge of menstrual, attitudes towards menstruation and menstrual practices. Data retrieval using a questionnaire in the google form. Results: The results shows 68% of respondents have high knowledge, 55,3% of respondents have negative attitudes and 50,5% of respondents have good menstrual practices. Conclusions: High knowledge of menstruation wasn’t comparable with negative attitudes towards menstruation so only half of the respondents have good practice.